2005
DOI: 10.1016/j.virol.2004.12.032
|View full text |Cite
|
Sign up to set email alerts
|

Ca2+ permeability of the plasma membrane induced by rotavirus infection in cultured cells is inhibited by tunicamycin and brefeldin A

Abstract: Rotavirus infection of cultured cells induces a progressive increase in plasma membrane permeability to Ca2+. The viral product responsible for this effect is not known. We have used tunicamycin and brefeldin A to prevent glycosylation and membrane traffic and study the involvement of viral glycoproteins, NSP4 and/or VP7, in rotavirus-infected HT29 and MA104 cells. In infected cells, we observed an increase of plasma membrane Ca2+ permeability and a progressive depletion of agonist-releasable ER pools measured… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
33
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(37 citation statements)
references
References 39 publications
4
33
0
Order By: Relevance
“…So far, several reports have shown that Ca 2ϩ -dependent apoptosis occurs following infections with viruses (10) such as hepatitis C virus (3), human T-cell leukemia virus type 1 (57), HIV (25,26,31), and rotavirus (56). In addition to these findings, we show here that H5N1-AIV infection induced an influx of extracellular Ca 2ϩ , leading to apoptosis of DEF.…”
Section: Discussionsupporting
confidence: 81%
“…So far, several reports have shown that Ca 2ϩ -dependent apoptosis occurs following infections with viruses (10) such as hepatitis C virus (3), human T-cell leukemia virus type 1 (57), HIV (25,26,31), and rotavirus (56). In addition to these findings, we show here that H5N1-AIV infection induced an influx of extracellular Ca 2ϩ , leading to apoptosis of DEF.…”
Section: Discussionsupporting
confidence: 81%
“…Further experiments, such as an evaluation of the NSP4 distribution within the cell in the absence of VP7, are required to differentiate between these possibilities. In a recent study, it was reported that rotavirus infection leads to a progressive depletion of ER pools released by agonists (32). Interestingly, in this work, such depletion was still observed when NSP4 was silenced, suggesting that this protein is not directly responsible for this effect.…”
Section: Discussionmentioning
confidence: 52%
“…It has recently been shown that in tunicamycin-treated, rotavirus-infected cells, the changes in Ca 2ϩ permeability of the plasma membrane are inhibited, thus suggesting that a glycosylated viral product, NSP4 or VP7, is responsible for such changes (32). NSP4 appears as a most likely candidate, given its several effects in Ca 2ϩ homeostasis.…”
Section: Rotavirus Infection Of Cells In Culture Induces Major Changementioning
confidence: 99%
See 2 more Smart Citations